Effect of internet use on relationship between civic participation and political participation among low-income urban youth in Malaysia - Samsuddin, Jamali (2019)
The issue of youth civic and political participation has been a substantive area of interest in academic research because active citizenship is the bedrock of a healthy and functioning democracy. But democracies around the world are in poor health because their young citizens are no longer “active.” Much evidence in this research area from the past decade has shown increasing detachment of young people from politics. Youth political apathy has become a global phenomenon that threatens to weaken democracies around the world, including Malaysia. The mobilization theory suggests that new communication technologies such as the Internet could increase participation, especially underprivileged group. Many past studies on the effect of Internet on youth’s democratic participation tend to treat young people as one homogeneous group, frequently sampled from the general youth population. However, not all youths have an equal access to opportunities to participate in nation-building activities. This study seeks new evidence in this area by focusing on youth living in low-income urban communities. It is important to focus on this particular segment of society as past studies have found that marginalization hindered their participation in social, political and economic processes. This quantitative study surveyed low-income urban youth to examine: (i) the level of their Internet use; (ii) the level of their political and civic participation; and (iii) the confounding effect of Internet use on the relationship between civic participation and political participation. A set of questionnaires were used as the instrument for data collection. The study employed a multistage sampling method, a combination of stratified random sampling and purposive sampling techniques. A total of 3,412 youths aged 15 to 25 years old living in urban poor areas throughout Malaysia completed the self-administered questionnaires. The results show that the level of their Internet use was low and still confined to basic activities. As anticipated, they rarely participated in political and civic activities; and there was a weak positive relationship between Internet use and participation. In addition, the observed relationship between civic participation and political participation was not merely due to the influence of Internet use.